A flame retardant smoke suppressant, preparation method and application thereof in PVC products
By preparing and mixing flame retardants such as intercalated magnesium aluminum hydrotalcite and hydroxylated starch, the problems of large amounts and poor dispersion of existing flame retardant smoke retardant are solved, the mechanical properties and high temperature stability of PVC products are improved, and the better flame retardant smoke retardant effect is achieved.
Patent Information
- Application Number
- CN202411764807.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-04
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2044-12-04
AI Technical Summary
The flame retardant and smoke deflator used in existing PVC products have problems such as large amounts, poor dispersion, poor compatibility, and still need to be used extensively during combustion, which affects the mechanical properties and high temperature stability of the products.
The first flame retardant is prepared by steps such as intercalation, coordination crosslinking and esterification, and the second flame retardant is prepared by steps such as hydroxylation, starch coating and crosslinking. The two are used mixed to improve the dispersion and compatibility of the flame retardant and smoke-retardant, reduce the amount and improve the flame retardant effect.
The flame retardant smoke degasser is not easy to agglomerate, the amount is small and the effect is good, the mechanical properties and high temperature stability of PVC products are improved, and the smoke generation can be effectively reduced during the combustion process.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of flame retardant smoke suppressants, and in particular to a flame retardant smoke suppressant, a preparation method and application thereof in PVC products. Background Art
[0002] Polyvinyl chloride, abbreviated as PVC in English, is a polymer formed by the polymerization of vinyl chloride monomer in the presence of initiators such as peroxides, azo compounds, or under the action of light or heat according to the free radical polymerization mechanism.
[0003] PVC is an amorphous white powder with a low degree of branching. It has the advantages of flame retardancy, chemical resistance, good electrical insulation and high mechanical strength, but poor high-temperature stability. Although PVC has good flame retardancy, during the combustion process, PVC first undergoes a dehydrochlorination reaction, and then a series of reactions such as cross-linking, cyclization, and chain scission occur. Continued combustion will generate carbon monoxide, carbon dioxide, benzene ring compounds, and carbon smoke, which cause great harm to the environment and personal safety. Among all general-purpose plastics and engineering plastics used, PVC is one of the plastics that produces the most smoke when burned.
[0004] In order to reduce the amount of smoke generated when PVC is burned, the most commonly used method is to add flame retardants and smoke suppressants to PVC. The commonly used flame retardants and smoke suppressants for PVC are molybdenum compounds, metal hydroxides, and borates. Among them, molybdenum compounds can form a stable, continuous, and dense carbon layer on the surface of PVC during the combustion process, preventing further contact between oxygen and the internal PVC, slowing down the combustion reaction, and inhibiting the escape of carbon smoke; they can also react with the free radicals generated by the combustion to interrupt the combustion chain reaction, thereby reducing the intensity of the combustion and the amount of smoke generated; in addition, molybdenum compounds can also form substances with special chemical structures at high temperatures to adsorb and capture the gases generated by PVC during the combustion process. During the combustion process, metal hydroxides can be decomposed into water and metal oxides by heat. Metal oxides have a large surface area and can absorb carbon soot and promote the formation of a carbon layer. The water formed by thermal decomposition can also be converted into water vapor to dilute the gas generated by PVC during the combustion process. In addition, metal hydroxides can also react with hydrogen chloride generated by PVC during the combustion process to reduce the release of hydrogen chloride. During the combustion process, borates can form a stable flame retardant layer on the surface of PVC to prevent further contact between oxygen and the internal PVC, slow down the combustion reaction, and inhibit the escape of carbon soot. They can also absorb the heat generated by PVC during the combustion process to inhibit the combustion. In addition, borates can also react with hydrogen chloride generated by PVC during the combustion process to reduce the release of hydrogen chloride.
[0005] The above-mentioned flame retardant and smoke suppressants, when used alone, all have the problem of large dosage and unsatisfactory flame retardant and smoke suppressant effect. Therefore, in the production of PVC products, multiple flame retardant and smoke suppressants are generally compounded and added to PVC products. Specifically, multiple flame retardant and smoke suppressants are mixed and crushed to obtain a compound flame retardant and smoke suppressant, which is mixed with PVC and processed into PVC products. However, this method has the following problems: First, in order to improve the dispersibility of the compound flame retardant and smoke suppressant, the flame retardant and smoke suppressant is generally required to be crushed into submicron powder, but the submicron powder has high surface activity and is easy to agglomerate; second, the compound flame retardant and smoke suppressant is an inorganic substance and has poor compatibility with PVC, which affects the mechanical strength of the prepared PVC products; third, during the combustion process, the compound flame retardant and smoke suppressant still needs to form a stable flame retardant layer on the surface of PVC to achieve the flame retardant and smoke suppressant effect. Therefore, a large amount of compound flame retardant and smoke suppressant is still required to achieve a better flame retardant and smoke suppressant effect.
[0006] In order to solve the above problems, the most commonly used method at present is to use surfactants or silane coupling agents to modify the surface of the compound flame retardant and smoke suppressant to reduce the agglomeration of the compound flame retardant and smoke suppressant and improve the compatibility of the compound flame retardant and smoke suppressant with PVC; and to add organic flame retardants to the compound flame retardant and smoke suppressant to reduce the amount of the compound flame retardant and smoke suppressant. However, surfactants, silane coupling agents, and organic flame retardants are prone to produce smoke during combustion, which affects the flame retardant and smoke suppressant effect of the compound flame retardant and smoke suppressant; organic flame retardants have poor heat resistance, which will further reduce the high temperature stability of PVC products. Summary of the invention
[0007] In view of the deficiencies in the prior art, the present invention provides a flame retardant and smoke suppressant, a preparation method and application thereof in PVC products. The flame retardant and smoke suppressant prepared by the present invention is not only not easy to agglomerate, but also has a small dosage and good flame retardant and smoke suppressant effect, and can also improve the mechanical properties and high temperature stability of PVC products.
[0008] In order to solve the above technical problems, the technical solution adopted by the present invention is as follows:
[0009] A method for preparing a flame retardant and smoke suppressant comprises the following steps: preparing a first flame retardant, preparing a second flame retardant, and mixing;
[0010] The preparation of the first flame retardant comprises the following steps: intercalation, coordination cross-linking, and esterification;
[0011] The intercalation comprises grinding magnesium aluminum hydrotalcite to obtain magnesium aluminum hydrotalcite powder, mixing the magnesium aluminum hydrotalcite powder and the first portion of water, and ultrasonically oscillating the mixture at room temperature, wherein the frequency of the ultrasonic oscillation is controlled to be 20-30 kHz and the time is 30-40 minutes to obtain a magnesium aluminum hydrotalcite powder suspension; mixing hexadecyl trimethyl ammonium bromide and the second portion of water, and stirring the mixture at room temperature at a stirring speed of 400-500 rpm for 30-40 minutes to obtain a hexadecyl trimethyl ammonium bromide aqueous solution; mixing polyvinyl alcohol 1799 and the third portion of water, and stirring the mixture at 80-85° C. and a stirring speed of 400-500 rpm for 50- 60min to obtain a polyvinyl alcohol aqueous solution; at 70-80°C, stirring the magnesium aluminum hydrotalcite powder suspension at a stirring speed of 500-600rpm for 1.5-2h, keeping the temperature and stirring speed unchanged, dripping a hexadecyltrimethylammonium bromide aqueous solution thereto, stirring for 4-5h after the dripping is completed, dripping a polyvinyl alcohol aqueous solution thereto, stirring for 6-7h after the dripping is completed, centrifuging at a centrifugal speed of 8000-9000rpm for 14-15min, taking a precipitate, washing it with water 2-3 times, and freeze-drying it at -40°C to -30°C for 24-25h to obtain an intercalated magnesium aluminum hydrotalcite;
[0012] In the intercalation layer, the particle size of the magnesium aluminum hydrotalcite powder is 250-300nm;
[0013] The mass ratio of the magnesium-aluminum hydrotalcite powder in the magnesium-aluminum hydrotalcite powder suspension to the first portion of water is 100-110:2100-2500;
[0014] The mass ratio of cetyltrimethylammonium bromide in the cetyltrimethylammonium bromide aqueous solution to the second portion of water is 8-10:80-100;
[0015] The mass ratio of polyvinyl alcohol 1799 in the polyvinyl alcohol aqueous solution to the third portion of water is 10-15:120-150;
[0016] The mass ratio of the magnesium aluminum hydrotalcite in the magnesium aluminum hydrotalcite suspension, the cetyl trimethyl ammonium bromide in the cetyl trimethyl ammonium bromide aqueous solution, and the polyvinyl alcohol 1799 in the polyvinyl alcohol aqueous solution is 100-110:8-10:10-15;
[0017] The dripping speed of the hexadecyltrimethylammonium bromide aqueous solution is 6-8 g / min;
[0018] The dropping speed of the polyvinyl alcohol aqueous solution is 7-10 g / min;
[0019] The coordination crosslinking comprises mixing the intercalated magnesium aluminum hydrotalcite and water, stirring at a stirring speed of 400-500 rpm for 40-50 minutes at room temperature, dropping a zinc chloride aqueous solution, continuing stirring for 1-1.5 hours after the dropping is completed, centrifuging at a centrifugal speed of 8000-9000 rpm for 14-15 minutes, taking a precipitate, washing it with water for 2-3 times, and freeze-drying it at -40°C to -30°C for 28-30 hours to obtain a coordinated crosslinked magnesium aluminum hydrotalcite;
[0020] In the coordination crosslinking, the mass ratio of intercalated magnesium aluminum hydrotalcite, water, and zinc chloride aqueous solution is 105-115:2400-2600:130-150;
[0021] The mass concentration of the zinc chloride aqueous solution is 10%;
[0022] The dropping speed of the zinc chloride aqueous solution is 6-8 g / min;
[0023] The esterification comprises mixing the coordinated cross-linked magnesium aluminum hydrotalcite, stearic acid, p-toluenesulfonic acid and toluene, stirring under reflux at 100-105° C. at a stirring speed of 300-400 rpm for 3-4 hours in a nitrogen atmosphere, centrifuging at a centrifugal speed of 8000-9000 rpm for 18-20 minutes, taking a precipitate, washing it with toluene 2-3 times, and drying it at 115-125° C. for 12-13 hours to obtain a first flame retardant;
[0024] In the esterification, the mass ratio of coordinated cross-linked magnesium aluminum hydrotalcite, stearic acid, p-toluenesulfonic acid, and toluene is 100-105:30-35:0.15-0.18:900-1000;
[0025] The preparation of the second flame retardant comprises the following steps: hydroxylation, starch coating, and cross-linking;
[0026] The hydroxylation comprises grinding ammonium octamolybdate and zinc borate separately to obtain ammonium octamolybdate powder and zinc borate powder, mixing the ammonium octamolybdate powder and the zinc borate powder, stirring at a stirring speed of 50-100 rpm for 20-30 minutes at room temperature to obtain a mixed powder; mixing polyvinyl alcohol 1799 and water, stirring at a stirring speed of 400-500 rpm for 50-60 minutes at 80-85° C., slowly adding the mixed powder, continuing to stir for 3-3.5 hours after the addition is completed, centrifuging at a centrifugal speed of 9000-10000 rpm for 14-15 minutes, taking a precipitate, washing it with water for 2-3 times, and drying it at 110-120° C. for 10-11 hours to obtain a hydroxylated mixed powder;
[0027] In the hydroxylation, the particle sizes of the ammonium octamolybdate powder and the zinc borate powder are both 200-250 nm;
[0028] The mass ratio of ammonium octamolybdate powder, zinc borate powder, polyvinyl alcohol 1799 and water is 50-55:70-80:30-35:800-900;
[0029] The mixing powder is added at a rate of 10-12 g / min;
[0030] The coated starch comprises mixing the hydroxylated mixed powder and the first portion of water, and then ultrasonically oscillating at room temperature, controlling the frequency of the ultrasonic oscillation to be 20-30 kHz, and the time to be 30-40 min, to obtain a hydroxylated mixed powder suspension; mixing the corn starch and the second portion of water, stirring at 800-90° C. and a stirring speed of 800-900 rpm for 40-50 min, slowly adding the hydroxylated mixed powder suspension, continuing to stir for 40-50 min after the addition is completed, standing at 3-5° C. for 18-20 h, centrifuging at a centrifugal speed of 10000-11000 rpm for 14-15 min, washing with water for 3-4 times, and drying at 110-120° C. for 13-15 h to obtain a mixed powder after the coated starch;
[0031] In the coated starch, the mass ratio of the hydroxylated mixed powder, the first portion of water, corn starch, and the second portion of water is 120-130:2200-2500:35-40:700-800;
[0032] The addition rate of the hydroxylated mixed powder suspension is 25-30 g / min;
[0033] The cross-linking comprises mixing sodium hexametaphosphate and the first portion of water, stirring at a stirring speed of 300-400rpm for 1.5-2h at room temperature to obtain a sodium hexametaphosphate aqueous solution; mixing the mixed powder coated with starch and the second portion of water, ultrasonically oscillating at room temperature, controlling the frequency of the ultrasonic oscillation to be 20-30kHz, and the time to be 30-40min to obtain a mixed powder suspension coated with starch; stirring the mixed powder suspension coated with starch at a stirring speed of 500-600rpm at 40-45°C, then dripping the sodium hexametaphosphate aqueous solution, continuing to stir for 20-30min after the dripping is completed, dripping the sodium hydroxide aqueous solution until the pH is 9-9.5, continuing to stir for 3-3.5h after the dripping is completed, centrifuging at a centrifugal speed of 9000-10000rpm for 14-15min, washing with water 3-4 times, and drying at 120-130°C for 15-16h to obtain a second flame retardant;
[0034] In the cross-linking, the mass ratio of sodium hexametaphosphate in the sodium hexametaphosphate aqueous solution to the first portion of water is 30-35:1500-1700;
[0035] The mass ratio of the mixed powder coated with starch to the second portion of water in the mixed powder suspension coated with starch is 135-145:3500-4000;
[0036] The mass ratio of the sodium hexametaphosphate in the sodium hexametaphosphate aqueous solution to the coated starch in the mixed powder suspension after the coated starch is 30-35:135-145;
[0037] The mass fraction of the sodium hydroxide aqueous solution is 10%;
[0038] The dropping speed of the sodium hexametaphosphate aqueous solution is 20-30 g / min;
[0039] The dropping speed of the sodium hydroxide aqueous solution is 15-20 g / min;
[0040] The mixing, after mixing the first flame retardant and the second flame retardant, is stirred at room temperature at a stirring speed of 50-100 rpm for 30-40 minutes to obtain a flame retardant smoke suppressant;
[0041] In the mixing, the mass ratio of the first flame retardant to the second flame retardant is 10-13:10.
[0042] A flame retardant and smoke suppressant obtained by the above-mentioned preparation method.
[0043] An application of the flame retardant and smoke suppressant obtained by the above-mentioned preparation method in PVC products, comprising uniformly mixing PVC resin, dioctyl sebacate, epoxy soybean oil, calcium stearate, flame retardant and smoke suppressant, antioxidant 1010, methyl methacrylate and methyl acrylate copolymer, adding the mixture to a kneader for kneading, adding the mixture to a twin-screw extruder for extrusion granulation, and then adding the mixture to a molding machine for molding to obtain a PVC product;
[0044] In the application of the flame retardant and smoke suppressant in PVC products, the mass ratio of PVC resin, dioctyl sebacate, epoxy soybean oil, calcium stearate, flame retardant and smoke suppressant, antioxidant 1010, methyl methacrylate and methyl acrylate copolymer is 90-110:18-20:4-5:4-6:5-6:0.2-0.3:1-1.2.
[0045] Compared with the prior art, the present invention has the following beneficial effects:
[0046] (1) The flame retardant smoke suppressant of the present invention is formed by mixing a first flame retardant and a second flame retardant, wherein the preparation method of the first flame retardant comprises intercalation, coordination crosslinking, and esterification, wherein the intercalation is performed by intercalating the magnesium aluminum hydrotalcite with polyhexadecyltrimethylammonium bromide to increase the interlayer spacing of the magnesium aluminum hydrotalcite, and then intercalating the magnesium aluminum hydrotalcite with polyvinyl alcohol to obtain the magnesium aluminum hydrotalcite intercalated with polyvinyl alcohol; the coordination crosslinking is performed by treating the magnesium aluminum hydrotalcite intercalated with polyvinyl alcohol with a zinc ion aqueous solution, wherein the zinc ions enter the interlayer of the magnesium aluminum hydrotalcite intercalated with polyvinyl alcohol, and produce a coordination effect with the hydroxyl group in the polyvinyl alcohol, thereby fixing the zinc ions in the interlayer of the magnesium aluminum hydrotalcite intercalated with polyvinyl alcohol, and obtaining the coordinated crosslinked magnesium aluminum hydrotalcite; and the esterification is performed by The invention discloses a first flame retardant with stearic acid and hydroxyl groups in coordinated cross-linked magnesium aluminum hydrotalcite that are not coordinated with zinc ions to obtain a first flame retardant with stearate ester bound to the surface; the polyvinyl alcohol in the first flame retardant is used as an intumescent flame retardant to accelerate the formation of a carbon layer, thereby playing a role in flame retardancy and heat insulation; the polyvinyl alcohol is intercalated into the magnesium aluminum hydrotalcite to adsorb carbon monoxide generated by the combustion of the polyvinyl alcohol, thereby reducing the generation of smoke during the combustion of PVC products; the zinc ions can fix the polyvinyl alcohol and generate zinc oxide during the combustion; the zinc oxide can improve the stability and density of the carbon layer and further adsorb the carbon monoxide generated by the combustion of the polyvinyl alcohol, thereby improving the flame retardancy and smoke suppression effect of the flame retardant and smoke suppressant and reducing the smoke generation of the flame retardant and smoke suppressant. The amount of the flame retardant is reduced; the stearate can reduce the hydrophilicity of the first flame retardant, improve the dispersibility of the first flame retardant, avoid the agglomeration of the first flame retardant, and improve the compatibility of the first flame retardant with PVC, thereby improving the mechanical strength and high-temperature stability of PVC products. During the combustion of PVC products, the stearate is decomposed into stearic acid and attached to the surface of the carbon layer, further improving the stability and density of the carbon layer, and reducing the amount of the flame retardant and smoke suppressant. The preparation method of the second flame retardant comprises hydroxylation, starch coating, and cross-linking, wherein the hydroxylation is to use polyvinyl alcohol to surface treat the mixed powder of ammonium octamolybdate powder and zinc borate powder, and the polyvinyl alcohol is adsorbed on the surface of the mixed powder of ammonium octamolybdate powder and zinc borate powder, thereby introducing hydroxyl groups to obtain hydroxyl groups. The base mixed powder is used for coating starch, and the gelatinized starch is bonded to the surface of the hydroxylated mixed powder through hydrogen bonds to obtain the mixed powder after coating starch; the cross-linking is carried out by cross-linking sodium hexametaphosphate with the starch on the surface of the mixed powder after coating starch to obtain the second flame retardant coated with cross-linked starch; the polyvinyl alcohol and the cross-linked starch in the second flame retardant are used as intumescent flame retardants, which can cooperate with each other to quickly form a stable carbon layer during the combustion process, and the ammonium octamolybdate powder and the zinc borate powder can absorb the carbon monoxide generated by the polyvinyl alcohol and the cross-linked starch during the combustion process, and the ammonium octamolybdate powder and the zinc borate powder can also improve the density of the carbon layer, thereby improving the flame retardant and smoke suppressant effect of the flame retardant and smoke suppressant, and reducing the amount of the flame retardant and smoke suppressant;Cross-linking starch with sodium hexametaphosphate can reduce the hydrophilicity of starch and improve the compatibility of starch with PVC, thereby avoiding the agglomeration of the second flame retardant and improving the mechanical properties and high-temperature stability of PVC products. The first flame retardant and the second flame retardant work together, and the flame retardant and smoke suppression principle of the first flame retardant and the second flame retardant cooperate to achieve a better flame retardant and smoke suppression effect;
[0047] (2) The flame retardant and smoke suppressant prepared by the present invention is not easy to agglomerate;
[0048] (3) The flame retardant and smoke suppressant prepared by the present invention has a small dosage and a good flame retardant and smoke suppressant effect. In the PVC product prepared by the flame retardant and smoke suppressant of the present invention, the mass fraction of the flame retardant and smoke suppressant is 4.04-4.09%, the limiting oxygen index of the PVC product is 37.1-37.8%, and the smoke density grade SDR is 21.0-22.9%;
[0049] (4) The flame retardant and smoke suppressant prepared by the present invention can improve the mechanical properties of PVC products. The tensile strength of the PVC products prepared by the flame retardant and smoke suppressant of the present invention is 14.6-15.5 MPa, and the elongation at break is 278-287%;
[0050] (5) The flame retardant and smoke suppressant prepared by the present invention can improve the high temperature stability of PVC products. After the PVC products prepared by the flame retardant and smoke suppressant of the present invention are placed in an environment at a temperature of 120°C for 1 hour, the tensile strength is 14.4-15.4MPa, the elongation at break is 273-281%, the limiting oxygen index is 37.0-37.8%, and the smoke density grade SDR is 21.1-22.6%. DETAILED DESCRIPTION
[0051] In order to have a clearer understanding of the technical features, purposes and effects of the present invention, the specific implementation methods of the present invention are now described.
[0052] Example 1
[0053] A method for preparing a flame retardant smoke suppressant, specifically comprising:
[0054] 1. Preparation of the first flame retardant:
[0055] (1) Intercalation: Grind magnesium aluminum hydrotalcite to a particle size of 250 nm to obtain magnesium aluminum hydrotalcite powder. Mix 100 g of magnesium aluminum hydrotalcite powder and 2100 g of water, and then ultrasonically vibrate at room temperature. The frequency of the ultrasonic vibration is controlled to be 20 kHz and the time is 30 min to obtain a magnesium aluminum hydrotalcite suspension. Mix 8 g of hexadecyltrimethylammonium bromide and 80 g of water, and stir at room temperature at a stirring speed of 400 rpm for 30 min to obtain a hexadecyltrimethylammonium bromide aqueous solution. Mix 10 g of polyvinyl alcohol 1799 and 120 g of water, and stir at 80°C at a stirring speed of 400 rpm for 50 min to obtain to a polyvinyl alcohol aqueous solution; at 70°C, stir the above-mentioned magnesium aluminum hydrotalcite suspension at a stirring speed of 500 rpm for 1.5 hours, keep the temperature and stirring speed unchanged, add the above-mentioned hexadecyltrimethylammonium bromide aqueous solution dropwise thereto, control the dropping speed to 6 g / min, continue stirring for 4 hours after the dropping is completed, add the above-mentioned polyvinyl alcohol aqueous solution dropwise thereto, control the dropping speed to 7 g / min, continue stirring for 6 hours after the dropping is completed, centrifuge at a centrifugal speed of 8000 rpm for 14 minutes, take the precipitate, wash it twice with water, and freeze-dry it at -40°C for 24 hours to obtain intercalated magnesium aluminum hydrotalcite;
[0056] (2) Coordination crosslinking: 105 g of intercalated magnesium aluminum hydrotalcite and 2400 g of water were mixed, stirred at 400 rpm for 40 min at room temperature, 130 g of 10% zinc chloride aqueous solution was added dropwise at a rate of 6 g / min, and stirring was continued for 1 h after the addition was completed. The mixture was centrifuged at 8000 rpm for 14 min, the precipitate was collected, washed twice with water, and freeze-dried at -40 °C for 28 h to obtain coordinated crosslinked magnesium aluminum hydrotalcite;
[0057] (3) Esterification: 100 g of coordinated cross-linked magnesium aluminum hydrotalcite, 30 g of stearic acid, 0.15 g of p-toluenesulfonic acid, and 900 g of toluene were mixed, and the mixture was refluxed and stirred at 100 ° C. and 300 rpm for 3 h in a nitrogen atmosphere, and centrifuged at 8000 rpm for 18 min. The precipitate was taken, washed twice with toluene, and dried at 115 ° C. for 12 h to obtain a first flame retardant;
[0058] 2. Preparation of the second flame retardant:
[0059] (1) Hydroxylation: ammonium octamolybdate and zinc borate were ground to a particle size of 200 nm to obtain ammonium octamolybdate powder and zinc borate powder. 50 g of ammonium octamolybdate powder and 70 g of zinc borate powder were mixed, and stirred at room temperature at a stirring speed of 50 rpm for 20 min to obtain a mixed powder. 30 g of polyvinyl alcohol 1799 and 800 g of water were mixed, and stirred at 80° C. at a stirring speed of 400 rpm for 50 min. All the mixed powders were slowly added at a rate of 10 g / min. After the addition was completed, stirring was continued for 3 h. The mixture was centrifuged at a centrifugal speed of 9000 rpm for 14 min. The precipitate was taken, washed twice with water, and dried at 110° C. for 10 h to obtain a hydroxylated mixed powder.
[0060] (2) Starch coating: 120 g of hydroxylated mixed powder and 2200 g of water were mixed, and ultrasonic oscillation was performed at room temperature, and the frequency of ultrasonic oscillation was controlled to be 20 kHz, and the time was 30 min to obtain a hydroxylated mixed powder suspension; 35 g of corn starch and 700 g of water were mixed, and the stirring speed was 800 rpm at 80°C for 40 min, and all the hydroxylated mixed powder suspension was slowly added, and the adding speed was controlled to be 25 g / min. After the addition was completed, stirring was continued for 40 min, and the mixture was allowed to stand at 3°C for 18 h, and centrifuged at a centrifugal speed of 10000 rpm for 14 min, and washed with water 3 times, and dried at 110°C for 13 h to obtain a mixed powder coated with starch;
[0061] (3) Cross-linking: 30 g of sodium hexametaphosphate and 1500 g of water were mixed, and the mixture was stirred at a stirring speed of 300 rpm for 1.5 h at room temperature to obtain a sodium hexametaphosphate aqueous solution; 135 g of the mixed powder coated with starch and 3500 g of water were mixed, and ultrasonic oscillation was performed at room temperature, and the frequency of the ultrasonic oscillation was controlled to be 20 kHz for 30 min to obtain a mixed powder suspension coated with starch; the mixed powder suspension coated with starch was stirred at a stirring speed of 500 rpm at 40°C, and then the sodium hexametaphosphate aqueous solution was added dropwise at a dropping speed of 20 g / min. After the addition was completed, the stirring was continued for 20 min. A 10% sodium hydroxide aqueous solution was added dropwise until the pH value was 9. The dropping speed was controlled to be 15 g / min. After the addition was completed, the stirring was continued for 3 h. The mixture was centrifuged at a centrifugal speed of 9000 rpm for 14 min, washed with water 3 times, and dried at 120°C for 15 h to obtain a second flame retardant;
[0062] 3. Mixing: After mixing the first flame retardant and the second flame retardant in a ratio of 10:10, stir at room temperature at a stirring speed of 50 rpm for 30 minutes to obtain a flame retardant and smoke suppressant.
[0063] This embodiment also provides a flame retardant and smoke suppressant obtained by the aforementioned preparation method.
[0064] The present embodiment also provides an application of the flame retardant and smoke suppressant obtained by the aforementioned preparation method in PVC products, specifically: PVC resin, dioctyl sebacate, epoxy soybean oil, calcium stearate, flame retardant and smoke suppressant, antioxidant 1010, methyl methacrylate and methyl acrylate copolymer are uniformly mixed in a mass ratio of 90:18:4:4:5:0.2:1, added to a kneader for kneading, added to a twin-screw extruder for extrusion granulation, and then added to a molding machine for molding to obtain a PVC product.
[0065] Example 2
[0066] A method for preparing a flame retardant smoke suppressant, specifically comprising:
[0067] 1. Preparation of the first flame retardant:
[0068] (1) Intercalation: Grind magnesium aluminum hydrotalcite to a particle size of 250 nm to obtain magnesium aluminum hydrotalcite powder. Mix 105 g of magnesium aluminum hydrotalcite powder and 2400 g of water, and then ultrasonically vibrate at room temperature. The frequency of the ultrasonic vibration is controlled to be 25 kHz and the time is 35 min to obtain a magnesium aluminum hydrotalcite suspension. Mix 9 g of hexadecyl trimethyl ammonium bromide and 90 g of water, and stir at room temperature at a stirring speed of 450 rpm for 35 min to obtain a hexadecyl trimethyl ammonium bromide aqueous solution. Mix 12 g of polyvinyl alcohol 1799 and 140 g of water, and stir at 82 ° C at a stirring speed of 450 rpm for 55 min to obtain a polyvinyl alcohol. Aqueous solution of ethylene glycol; at 75°C, stir the above-mentioned magnesium aluminum hydrotalcite suspension at a stirring speed of 550 rpm for 1.5 hours, keep the temperature and stirring speed unchanged, add the above-mentioned aqueous solution of hexadecyltrimethylammonium bromide dropwise thereto, control the dropping speed to 7 g / min, continue stirring for 4.5 hours after the addition is completed, add the above-mentioned aqueous solution of polyvinyl alcohol dropwise thereto, control the dropping speed to 8 g / min, continue stirring for 6.5 hours after the addition is completed, centrifuge at a centrifugal speed of 8500 rpm for 15 minutes, take the precipitate, wash it twice with water, and freeze-dry it at -35°C for 24 hours to obtain intercalated magnesium aluminum hydrotalcite;
[0069] (2) Coordination crosslinking: 110 g of intercalated magnesium aluminum hydrotalcite and 2500 g of water were mixed, stirred at 450 rpm for 45 min at room temperature, 140 g of 10% zinc chloride aqueous solution was added dropwise at a rate of 7 g / min, stirring was continued for 1.5 h after the addition was completed, and the mixture was centrifuged at 8500 rpm for 15 min. The precipitate was taken, washed twice with water, and freeze-dried at -35 °C for 29 h to obtain coordinated crosslinked magnesium aluminum hydrotalcite;
[0070] (3) Esterification: 102 g of coordinated cross-linked magnesium aluminum hydrotalcite, 32 g of stearic acid, 0.17 g of p-toluenesulfonic acid, and 950 g of toluene were mixed, and the mixture was refluxed and stirred at 350 rpm for 3.5 h at 105 ° C in a nitrogen atmosphere, and centrifuged at 8500 rpm for 19 min. The precipitate was taken, washed twice with toluene, and dried at 120 ° C for 12.5 h to obtain a first flame retardant;
[0071] 2. Preparation of the second flame retardant:
[0072] (1) Hydroxylation: ammonium octamolybdate and zinc borate were ground to a particle size of 200 nm to obtain ammonium octamolybdate powder and zinc borate powder. 52 g of ammonium octamolybdate powder and 75 g of zinc borate powder were mixed, and the mixture was stirred at 80 rpm for 25 min at room temperature to obtain a mixed powder. 32 g of polyvinyl alcohol 1799 and 850 g of water were mixed, and the mixture was stirred at 450 rpm for 55 min at 82°C. The mixed powder was slowly added to the mixture at a rate of 11 g / min. After the addition was completed, the mixture was stirred for 3 h. The mixture was centrifuged at 9500 rpm for 15 min. The precipitate was collected, washed twice with water, and dried at 115°C for 10.5 h to obtain a hydroxylated mixed powder.
[0073] (2) Starch coating: 125 g of hydroxylated mixed powder and 2300 g of water were mixed, and ultrasonic oscillation was performed at room temperature, and the frequency of ultrasonic oscillation was controlled to be 25 kHz, and the time was 35 min to obtain a hydroxylated mixed powder suspension; 38 g of corn starch and 750 g of water were mixed, and the stirring speed was 850 rpm at 85°C for 45 min, and all the hydroxylated mixed powder suspension was slowly added, and the adding speed was controlled to be 28 g / min. After the addition was completed, stirring was continued for 45 min, and the mixture was allowed to stand at 4°C for 19 h, and centrifuged at a centrifugal speed of 10000 rpm for 15 min, and washed with water 3 times, and dried at 115°C for 14 h to obtain a mixed powder coated with starch;
[0074] (3) Cross-linking: 32 g of sodium hexametaphosphate and 1600 g of water were mixed, and the mixture was stirred at a stirring speed of 350 rpm for 1.5 h at room temperature to obtain a sodium hexametaphosphate aqueous solution; 140 g of the mixed powder coated with starch and 3800 g of water were mixed, and ultrasonic oscillation was performed at room temperature, and the frequency of the ultrasonic oscillation was controlled to be 25 kHz and the time was 35 min to obtain a mixed powder suspension coated with starch; the mixed powder suspension coated with starch was stirred at a stirring speed of 550 rpm at 42°C, and then the sodium hexametaphosphate aqueous solution was added dropwise, and the dropping speed was controlled to be 25 g / min. After the dropping was completed, the stirring was continued for 25 min. A 10% sodium hydroxide aqueous solution was added dropwise until the pH value was 9, and the dropping speed was controlled to be 20 g / min. After the dropping was completed, the stirring was continued for 3 h. The mixture was centrifuged at a centrifugal speed of 9500 rpm for 15 min, washed with water 3 times, and dried at 125°C for 15.5 h to obtain a second flame retardant;
[0075] 3. Mixing: After mixing the first flame retardant and the second flame retardant in a ratio of 12:10, stir at room temperature at a stirring speed of 80 rpm for 35 minutes to obtain a flame retardant and smoke suppressant.
[0076] This embodiment also provides a flame retardant and smoke suppressant obtained by the aforementioned preparation method.
[0077] The present embodiment also provides an application of the flame retardant and smoke suppressant obtained by the aforementioned preparation method in PVC products, specifically: PVC resin, dioctyl sebacate, epoxy soybean oil, calcium stearate, flame retardant and smoke suppressant, antioxidant 1010, methyl methacrylate and methyl acrylate copolymer are mixed uniformly in a mass ratio of 100:19:4.5:5:5.5:0.2:1.1, added to a kneader for kneading, added to a twin-screw extruder for extrusion granulation, and then added to a molding machine for molding to obtain a PVC product.
[0078] Example 3
[0079] A method for preparing a flame retardant smoke suppressant, specifically comprising:
[0080] 1. Preparation of the first flame retardant:
[0081] (1) Intercalation: Grind magnesium aluminum hydrotalcite to a particle size of 300 nm to obtain magnesium aluminum hydrotalcite powder. Mix 110 g of magnesium aluminum hydrotalcite powder and 2500 g of water, and then ultrasonically vibrate at room temperature. The frequency of the ultrasonic vibration is controlled to be 30 kHz and the time is 40 min to obtain a magnesium aluminum hydrotalcite suspension. Mix 10 g of hexadecyltrimethylammonium bromide and 100 g of water, and stir at room temperature at a stirring speed of 500 rpm for 40 min to obtain a hexadecyltrimethylammonium bromide aqueous solution. Mix 15 g of polyvinyl alcohol 1799 and 150 g of water, and stir at 85°C at a stirring speed of 500 rpm for 60 min. Obtain a polyvinyl alcohol aqueous solution; stir the above-mentioned magnesium aluminum hydrotalcite powder suspension at a stirring speed of 600 rpm at 80°C for 2 hours, keep the temperature and stirring speed unchanged, add the above-mentioned hexadecyltrimethylammonium bromide aqueous solution dropwise thereto, control the dropping speed to 8 g / min, continue stirring for 5 hours after the dropping is completed, add the above-mentioned polyvinyl alcohol aqueous solution dropwise thereto, control the dropping speed to 10 g / min, continue stirring for 7 hours after the dropping is completed, centrifuge at a centrifugal speed of 9000 rpm for 15 minutes, take the precipitate, wash it with water 3 times, and freeze-dry it at -30°C for 25 hours to obtain intercalated magnesium aluminum hydrotalcite;
[0082] (2) Coordination crosslinking: 115 g of intercalated magnesium aluminum hydrotalcite and 2600 g of water were mixed, stirred at 500 rpm for 50 min at room temperature, 150 g of 10% zinc chloride aqueous solution was added dropwise at a rate of 8 g / min, stirring was continued for 1.5 h after the addition was completed, and the mixture was centrifuged at 9000 rpm for 15 min. The precipitate was collected, washed with water for 3 times, and freeze-dried at -30 °C for 30 h to obtain coordinated crosslinked magnesium aluminum hydrotalcite;
[0083] (3) Esterification: 105 g of coordinated cross-linked magnesium aluminum hydrotalcite, 35 g of stearic acid, 0.18 g of p-toluenesulfonic acid, and 1000 g of toluene were mixed, and the mixture was refluxed and stirred at 400 rpm for 4 h at 105 ° C in a nitrogen atmosphere, and centrifuged at 9000 rpm for 20 min. The precipitate was taken, washed with toluene three times, and dried at 125 ° C for 13 h to obtain a first flame retardant;
[0084] 2. Preparation of the second flame retardant:
[0085] (1) Hydroxylation: ammonium octamolybdate and zinc borate were ground to a particle size of 250 nm to obtain ammonium octamolybdate powder and zinc borate powder. 55 g of ammonium octamolybdate powder and 80 g of zinc borate powder were mixed, and the mixture was stirred at room temperature at a stirring speed of 100 rpm for 30 min to obtain a mixed powder. 35 g of polyvinyl alcohol 1799 and 900 g of water were mixed, and the mixture was stirred at 85° C. at a stirring speed of 500 rpm for 60 min. The above mixed powder was slowly added at a rate of 12 g / min. After the addition was completed, the mixture was stirred for 3.5 h. The mixture was centrifuged at a centrifugal speed of 10,000 rpm for 15 min. The precipitate was taken, washed with water 3 times, and dried at 120° C. for 11 h to obtain a hydroxylated mixed powder.
[0086] (2) Starch coating: 130 g of hydroxylated mixed powder and 2500 g of water were mixed, and ultrasonic oscillation was performed at room temperature, and the frequency of ultrasonic oscillation was controlled to be 30 kHz, and the time was 40 min to obtain a hydroxylated mixed powder suspension; 40 g of corn starch and 800 g of water were mixed, and the stirring speed was 900 rpm at 90°C for 50 min, and all the hydroxylated mixed powder suspension was slowly added, and the adding speed was controlled to be 30 g / min. After the addition was completed, stirring was continued for 50 min, and the mixture was allowed to stand at 5°C for 20 h, and centrifuged at a centrifugal speed of 11000 rpm for 15 min, and washed with water 4 times, and dried at 120°C for 15 h to obtain a mixed powder coated with starch;
[0087] (3) Cross-linking: 35 g of sodium hexametaphosphate and 1700 g of water were mixed, and the mixture was stirred at a stirring speed of 400 rpm for 2 h at room temperature to obtain a sodium hexametaphosphate aqueous solution; 145 g of the mixed powder coated with starch and 4000 g of water were mixed, and ultrasonic oscillation was performed at room temperature, and the frequency of the ultrasonic oscillation was controlled to be 30 kHz for 40 min to obtain a mixed powder suspension coated with starch; the mixed powder suspension coated with starch was stirred at a stirring speed of 600 rpm at 45°C, and then the sodium hexametaphosphate aqueous solution was added dropwise, and the dropping speed was controlled to be 30 g / min. After the dropping was completed, the stirring was continued for 30 min. A 10% sodium hydroxide aqueous solution was added dropwise until the pH value was 9.5, and the dropping speed was controlled to be 20 g / min. After the dropping was completed, the stirring was continued for 3.5 h. The mixture was centrifuged at a centrifugal speed of 10000 rpm for 15 min, washed with water 4 times, and dried at 130°C for 16 h to obtain a second flame retardant;
[0088] 3. Mixing: After mixing the first flame retardant and the second flame retardant in a ratio of 13:10, stir at room temperature at a stirring speed of 100 rpm for 40 minutes to obtain a flame retardant and smoke suppressant.
[0089] This embodiment also provides a flame retardant and smoke suppressant obtained by the aforementioned preparation method.
[0090] The present embodiment also provides an application of the flame retardant and smoke suppressant obtained by the aforementioned preparation method in PVC products, specifically: PVC resin, dioctyl sebacate, epoxy soybean oil, calcium stearate, flame retardant and smoke suppressant, antioxidant 1010, methyl methacrylate and methyl acrylate copolymer are uniformly mixed in a mass ratio of 110:20:5:6:6:0.3:1.2, added to a kneader for kneading, added to a twin-screw extruder for extrusion granulation, and then added to a molding machine for molding to obtain a PVC product.
[0091] Comparative Example 1
[0092] Based on the preparation method of the flame retardant and smoke suppressant of Example 1, in the preparation of the first flame retardant in step 1, the coordination crosslinking step (2) and the esterification step (3) are omitted, that is, the intercalated magnesium aluminum hydrotalcite obtained by intercalation in step (1) is used as the first flame retardant and is directly used in the mixing in step 3.
[0093] This comparative example also provides a flame retardant and smoke suppressant obtained by the aforementioned preparation method.
[0094] This comparative example also provides an application of the flame retardant and smoke suppressant obtained by the aforementioned preparation method in PVC products, and the specific application method is the same as that in Example 1.
[0095] Comparative Example 2
[0096] Based on the preparation method of the flame retardant and smoke suppressant of Example 1, the second step of preparing the second flame retardant is omitted, and in the mixing in the third step, an equal amount of a mixed powder of ammonium octamolybdate powder and zinc borate powder is used to replace the second flame retardant, and the mass ratio of ammonium octamolybdate powder to zinc borate powder in the mixed powder of ammonium octamolybdate powder and zinc borate powder is 50:70.
[0097] This comparative example also provides a flame retardant and smoke suppressant obtained by the aforementioned preparation method.
[0098] This comparative example also provides an application of the flame retardant and smoke suppressant obtained by the aforementioned preparation method in PVC products, and the specific application method is the same as that in Example 1.
[0099] Comparative Example 3
[0100] Based on the preparation method of the flame retardant and smoke suppressant of Example 1, in the preparation of the first flame retardant in step 1, the coordination crosslinking step (2) and the esterification step (3) are omitted, that is, the intercalated magnesium aluminum hydrotalcite obtained by intercalation in step (1) is used as the first flame retardant and is directly used in the mixing in step 3.
[0101] This comparative example also provides a flame retardant and smoke suppressant obtained by the aforementioned preparation method.
[0102] This comparative example also provides an application of the flame retardant and smoke suppressant obtained by the aforementioned preparation method in PVC products, specifically: PVC resin, dioctyl sebacate, epoxy soybean oil, calcium stearate, flame retardant and smoke suppressant, antioxidant 1010, methyl methacrylate and methyl acrylate copolymer are mixed uniformly in a mass ratio of 90:18:4:4:7.5:0.2:1, added to a kneader for kneading, added to a twin-screw extruder for extrusion granulation, and then added to a molding machine for molding to obtain a PVC product.
[0103] The dosage of flame retardant and smoke suppressant will be adjusted to 1.5 times of the original amount.
[0104] Comparative Example 4
[0105] Based on the preparation method of the flame retardant and smoke suppressant of Example 1, the second step of preparing the second flame retardant is omitted, and in the mixing in the third step, an equal amount of a mixed powder of ammonium octamolybdate powder and zinc borate powder is used to replace the second flame retardant, and the mass ratio of ammonium octamolybdate powder to zinc borate powder in the mixed powder of ammonium octamolybdate powder and zinc borate powder is 50:70.
[0106] This comparative example also provides a flame retardant and smoke suppressant obtained by the aforementioned preparation method.
[0107] This comparative example also provides an application of the flame retardant and smoke suppressant obtained by the aforementioned preparation method in PVC products, specifically: PVC resin, dioctyl sebacate, epoxy soybean oil, calcium stearate, flame retardant and smoke suppressant, antioxidant 1010, methyl methacrylate and methyl acrylate copolymer are mixed uniformly in a mass ratio of 90:18:4:4:7.5:0.2:1, added to a kneader for kneading, added to a twin-screw extruder for extrusion granulation, and then added to a molding machine for molding to obtain a PVC product.
[0108] The dosage of flame retardant and smoke suppressant will be adjusted to 1.5 times of the original amount.
[0109] Performance Test 1
[0110] 200 g of the flame retardant and smoke suppressant obtained in Examples 1-3 and Comparative Examples 1-2 were respectively put into 1 kg packaging bags and left open. After being left open for 1 day in an environment with a temperature of 25° C. and a relative humidity of 70%, the agglomeration problem was observed. The observation results are as follows:
[0111]
[0112] Performance Test 2
[0113] The oxygen index, combustion smoke emission, tensile strength and elongation at break of the PVC products obtained in Examples 1-3 and Comparative Examples 1-4 were tested, and the test results are as follows:
[0114]
[0115] Performance Test 3
[0116] The PVC products obtained in Examples 1-3 and Comparative Examples 1-4 were placed in an environment at a temperature of 120° C. for 1 hour, and then the oxygen index, combustion smoke emission, tensile strength, and elongation at break of the PVC products were tested. The test results are as follows:
[0117]
[0118] It can be seen from the above results that by coordinating, cross-linking and esterifying the polyvinyl alcohol intercalated magnesium aluminum hydrotalcite in the preparation of the first flame retardant, and hydroxylating, coating starch and cross-linking the mixed powder of ammonium octamolybdate powder and zinc borate powder in the preparation of the second flame retardant, the agglomeration of the prepared flame retardant and smoke suppressant can be avoided, the amount of the flame retardant and smoke suppressant can be reduced, the effect of the flame retardant and smoke suppressant can be improved, and the mechanical properties and high temperature stability of the PVC products prepared from the flame retardant and smoke suppressant can be improved.
[0119] Unless otherwise specified, all percentages used in the present invention are by mass.
[0120] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing a flame retardant and smoke suppressant, characterized in that: The method comprises the following steps: preparing a first flame retardant, preparing a second flame retardant, and mixing; The preparation of the first flame retardant comprises the following steps: intercalation, coordination cross-linking, and esterification; The intercalation comprises grinding magnesium aluminum hydrotalcite to obtain magnesium aluminum hydrotalcite powder, mixing the magnesium aluminum hydrotalcite powder and the first portion of water to obtain a magnesium aluminum hydrotalcite powder suspension; mixing hexadecyl trimethyl ammonium bromide and the second portion of water to obtain a hexadecyl trimethyl ammonium bromide aqueous solution; mixing polyvinyl alcohol 1799 and the third portion of water to obtain a polyvinyl alcohol aqueous solution; stirring the magnesium aluminum hydrotalcite powder suspension at 70-80° C., adding the hexadecyl trimethyl ammonium bromide aqueous solution dropwise thereto, continuing to stir after the addition, adding the polyvinyl alcohol aqueous solution dropwise thereto, continuing to stir after the addition, centrifuging, taking the precipitate, washing, and freeze-drying to obtain an intercalated magnesium aluminum hydrotalcite; In the intercalation layer, the mass ratio of the magnesium aluminum hydrotalcite in the magnesium aluminum hydrotalcite suspension, the hexadecyl trimethyl ammonium bromide in the hexadecyl trimethyl ammonium bromide aqueous solution, and the polyvinyl alcohol 1799 in the polyvinyl alcohol aqueous solution is 100-110:8-10:10-15; The coordination crosslinking comprises mixing the intercalated magnesium aluminum hydrotalcite and water, stirring at room temperature, dropping a zinc chloride aqueous solution, continuing to stir after the dropping is completed, centrifuging, taking a precipitate, washing, and freeze-drying to obtain the coordination crosslinked magnesium aluminum hydrotalcite; In the coordination crosslinking, the mass ratio of intercalated magnesium aluminum hydrotalcite, water, and zinc chloride aqueous solution is 105-115:2400-2600:130-150; The esterification comprises mixing the coordinated cross-linked magnesium aluminum hydrotalcite, stearic acid, p-toluenesulfonic acid and toluene, stirring under reflux at 100-105° C. in a nitrogen atmosphere, centrifuging, taking the precipitate, washing and drying to obtain the first flame retardant; In the esterification, the mass ratio of coordinated cross-linked magnesium aluminum hydrotalcite, stearic acid, p-toluenesulfonic acid, and toluene is 100-105:30-35:0.15-0.18:900-1000; The preparation of the second flame retardant comprises the following steps: hydroxylation, starch coating, and cross-linking; In the hydroxylation, ammonium octamolybdate and zinc borate are ground separately to obtain ammonium octamolybdate powder and zinc borate powder, and the ammonium octamolybdate powder and the zinc borate powder are evenly mixed to obtain a mixed powder; polyvinyl alcohol 1799 and water are mixed, stirred at 80-85° C., and the mixed powder is added, and stirring is continued after the addition is completed, centrifugation is performed, and the precipitate is taken, washed, and dried to obtain a hydroxylated mixed powder; In the hydroxylation, the mass ratio of ammonium octamolybdate powder, zinc borate powder, polyvinyl alcohol 1799, and water is 50-55:70-80:30-35:800-900; The starch coating comprises mixing the hydroxylated mixed powder and the first portion of water evenly to obtain a hydroxylated mixed powder suspension; mixing corn starch and the second portion of water, stirring at 80-90° C., adding the hydroxylated mixed powder suspension, continuing to stir after the addition, standing at 3-5° C., centrifuging, taking the precipitate, washing, and drying to obtain the starch coated mixed powder; In the coated starch, the mass ratio of the hydroxylated mixed powder, the first portion of water, corn starch, and the second portion of water is 120-130:2200-2500:35-40:700-800; The cross-linking comprises mixing sodium hexametaphosphate and the first portion of water evenly to obtain a sodium hexametaphosphate aqueous solution; mixing the mixed powder coated with starch and the second portion of water evenly to obtain a mixed powder suspension coated with starch; stirring the mixed powder suspension coated with starch at 40-45° C., then dripping the sodium hexametaphosphate aqueous solution, continuing to stir after the dripping is completed, adjusting the pH to 9-9.5, and then continuing to stir, centrifuging, taking the precipitate, washing, and drying to obtain a second flame retardant; During the cross-linking, the mass ratio of the sodium hexametaphosphate in the sodium hexametaphosphate aqueous solution to the coated starch in the mixed powder suspension after the coated starch is 30-35:135-145; The mixing evenly mixes the first flame retardant and the second flame retardant to obtain a flame retardant and smoke suppressant; In the mixing, the mass ratio of the first flame retardant to the second flame retardant is 10-13:
10.
2. The method for preparing the flame retardant and smoke suppressant according to claim 1, characterized in that: In the intercalation layer, the particle size of the magnesium aluminum hydrotalcite powder is 250-300nm; The mass ratio of the magnesium-aluminum hydrotalcite powder in the magnesium-aluminum hydrotalcite powder suspension to the first portion of water is 100-110:2100-2500; The mass ratio of cetyltrimethylammonium bromide in the cetyltrimethylammonium bromide aqueous solution to the second portion of water is 8-10:80-100; The mass ratio of polyvinyl alcohol 1799 in the polyvinyl alcohol aqueous solution to the third portion of water is 10-15:120-150; The dripping speed of the hexadecyltrimethylammonium bromide aqueous solution is 6-8 g / min; The dropping speed of the polyvinyl alcohol aqueous solution is 7-10 g / min.
3. The method for preparing the flame retardant and smoke suppressant according to claim 1, characterized in that: In the coordination crosslinking, the mass concentration of the zinc chloride aqueous solution is 10%; The dropping speed of the zinc chloride aqueous solution is 6-8 g / min.
4. The method for preparing the flame retardant and smoke suppressant according to claim 1, characterized in that: In the hydroxylation, the particle sizes of the ammonium octamolybdate powder and the zinc borate powder are both 200-250 nm; The adding speed of the mixed powder is 10-12g / min.
5. The method for preparing the flame retardant and smoke suppressant according to claim 1, characterized in that: In the coated starch, the hydroxylated mixed powder suspension is added at a speed of 25-30 g / min.
6. The method for preparing the flame retardant and smoke suppressant according to claim 1, characterized in that: In the cross-linking, the mass ratio of sodium hexametaphosphate in the sodium hexametaphosphate aqueous solution to the first portion of water is 30-35:1500-1700; The mass ratio of the mixed powder coated with starch to the second portion of water in the mixed powder suspension coated with starch is 135-145:3500-4000; The dropping speed of the sodium hexametaphosphate aqueous solution is 20-30 g / min.
7. A flame retardant and smoke suppressant obtained by the preparation method according to any one of claims 1 to 6.
8. Use of the flame retardant and smoke suppressant obtained by the preparation method according to any one of claims 1 to 6 in PVC products, characterized in that: The PVC resin, dioctyl sebacate, epoxy soybean oil, calcium stearate, flame retardant smoke suppressant, antioxidant 1010, methyl methacrylate and methyl acrylate copolymer are uniformly mixed, added to a kneader for kneading, added to a twin-screw extruder for extrusion granulation, and then added to a molding machine for molding to obtain a PVC product; In the application of the flame retardant and smoke suppressant in PVC products, the mass ratio of PVC resin, dioctyl sebacate, epoxy soybean oil, calcium stearate, flame retardant and smoke suppressant, antioxidant 1010, methyl methacrylate and methyl acrylate copolymer is 90-110:18-20:4-5:4-6:5-6:0.2-0.3:1-1.2.
Citation Information
Patent Citations
Low-smoke halogen-free flame-retardant sealing strip and method for preparing same
CN107057199A
Highly-flame-retardant polyvinyl chloride cable material and preparation method thereof
CN109206786A